Survival outcomes of hybrid total hip replacement following failed proximal femoral nail antirotation: a retrospective study with a median 10-year follow-up - Chen, Yannan; Lai, Zhifen; Yu, Weiguang; Zeng, Xianshang; Zhao, Mingdong; Zhu, Guangquan (Frontiers in Surgery, 2025)
BackgroundThis retrospective study evaluates the efficacy of hybrid total hip replacement (THR) in patients aged 50 to 70 years who have experienced failures following proximal femoral nail antirotation (PFNA) procedures. By addressing a significant gap in the current medical literature—characterized by inadequate data and inconsistencies regarding the effectiveness of hybrid THRs in revision settings—this research aims to provide valuable insights into the long-term viability and clinical outcomes of hybrid THR for this demographic.MethodsIn this retrospective observational study, we investigated 185 individuals aged 50 to 70 years who underwent hybrid THRs following PFNA procedures across two specialized Joint Surgery Centers. The primary objective of this study was to evaluate implant longevity, which was assessed using the Kaplan–Meier method, with a particular focus on revision surgeries. Additionally, we aimed to analyze secondary outcomes, including patient-reported experiences quantified by the EuroQol Visual Analogue Scale (EQ-VAS) and the Likert pain scale. Furthermore, this study sought to quantify the rates of major orthopedic complications within this patient cohort.ResultsA total of 124 individuals (124 THRs) were assessed, resulting in a median follow-up duration of 10 years (range: 3–15 years). The 10-year survivorship, defined as the rate of survival without revision for any reason, was found to be 87.1% (78.5%–90.1%). Stratified survival analysis by age groups (50–60 years and 60–70 years) revealed that the 50–60-year group had significantly higher survival rates compared to the 60–70-year group (p = 0.00026). Postoperative pain scores averaged 3.0 (95% CI, 2.9–3.1), indicating a significant reduction in pain. Furthermore, patient satisfaction was high, with an average satisfaction score of 3.7 (95% CI, 3.6–3.8). The mean EQ-VAS score was 77.4 (95% CI, 76.4–78.3), reflecting favorable post-surgical health perceptions. Among the 124 patients, 13 experienced a total of 19 implant-related complications, leading to an incidence rate of 10.4% for major orthopedic complications.ConclusionHybrid THR shows durable efficacy in patients aged 50–70 with failed PFNA, achieving high revision-free survival and improved postoperative outcomes. Younger patients (50–60 years) had superior survival, while Staphylococcus/Enterococcus infections worsened prognosis. Non-infected individuals aged 50–60 achieved optimal 10-year survival. Complications like stem loosening were reduced, but cement degradation and infection risks remain challenges. Future efforts should target age-specific protocols and infection mitigation.